Pareto and Elias Facing the Crisis of Contemporary Society - Bianco, Adele (Italian Sociological Review, 2024)
The purpose of this paper is to compare Vilfredo Pareto and Norbert Elias. Although they differ in many ways, the juxtaposition between the two sociologists provides useful elements to analyze crisis in contemporary society. The distance between their theoretical and thematic approaches can be an innovative driver, fostering a comprehensive analysis of contemporary society. The paper is structured as follows. The first section explains the reasons for juxtaposing the two authors, highlighting useful elements for our objective. The second section focuses on Pareto’s contribution to the current crisis of democracy and the rise of populism, identifying their roots and historical continuity. Factors of such “political decivilization” are, in some respect, more serious today than in Pareto’s time. The third section begins with Elias’ notion of “decivilization”. The analysis focuses on the regressive phenomena of our civilization, such as the rise of irrational behaviour, questioning the competence of experts, and the rejection of science. It also highlights worldviews that rely on imagination rather than on factual data, which can be surprising and disconcerting.